2019
DOI: 10.1016/j.mayocpiqo.2019.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugammadex on Time of First Postoperative Bowel Movement

Abstract: Objective To determine whether time to first postoperative bowel movement after intraperitoneal surgery differs among neuromuscular blockade reversal with either anticholinesterase/anticholinergic combination vs sugammadex. Patients and Methods Sugammadex was introduced to our practice in October 2016. Patients were identified who underwent intraperitoneal surgery between January 1, through June 30, 2016, and January 1 through June 30, 2017, and received aminosteroid ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 19 publications
1
34
4
Order By: Relevance
“…and neostigmine following open thyroidectomy. However, a recent retrospective study revealed that sugammadex was associated to earlier rst postoperative bowel movement than the combination of neostigmine and glycopyrrolate in patients undergoing intraperitoneal surgery [11]. In the current study, the median rst gas-passing time in the sugammadex group was shorter than in the neostigmine group [600 min.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…and neostigmine following open thyroidectomy. However, a recent retrospective study revealed that sugammadex was associated to earlier rst postoperative bowel movement than the combination of neostigmine and glycopyrrolate in patients undergoing intraperitoneal surgery [11]. In the current study, the median rst gas-passing time in the sugammadex group was shorter than in the neostigmine group [600 min.…”
Section: Discussioncontrasting
confidence: 53%
“…In intraperitoneal surgery, sugammadex does seem to accelerate bowel movement [10,11], but in nonintraperitoneal surgery, such as thyroidectomy, sugammadex and neostigmine/glycopyrrolate did not show signi cant differences in bowel movement. The difference between intraperitoneal and nonintraperitoneal surgery consists in the manipulation of the bowel during surgery.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, the effects of glycopyrrolate on delayed gastric emptying are greater than those of atropine [5]. Contrary to the 2 favorable studies on reversal with sugammadex [1,2], atropine was administered along with neostigmine for neuromuscular block reversal in the study by Sen et al [3], revealing no association between the neuromuscular reversal technique and the recovery time for postoperative bowel function.…”
mentioning
confidence: 97%